Low-carbon high-impedance cement-based material based on steel slag-hollow microbead-limestone calcined clay cement system and preparation method of low-carbon high-impedance cement-based material
By using steel slag-hollow microbeads-limestone calcined clay cement system in cement-based materials, the problem of insufficient durability and impedance of cement-based materials in rail transit when facing stray currents and groundwater erosion is solved, and low-carbon, high-impedance and durability cement-based materials are achieved, which are suitable for rail transit scenarios.
Patent Information
- Application Number
- CN202411834738.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to provide cement-based materials with both high impedance and durability in rail transit scenarios, especially when facing the dual challenges of stray currents and groundwater erosion.
Low-carbon high-impedance cement-based materials based on the steel slag-hollow microbead-limestone calcined clay cement system are used to partially replace cement or aggregate by incorporating limestone calcined clay cement, hollow glass microbeads and carbide steel slag, and the appropriate amount of each component is adjusted to improve resistivity and mechanical properties.
It has achieved the reduction of carbon dioxide emissions, improved the resistivity and mechanical properties of cement-based materials, and extended the service life of the structure. It is suitable for rail transit scenarios.
Smart Images

Figure CN119683930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cement-based materials, and in particular to a low-carbon high-impedance cement-based material based on a steel slag-hollow microsphere-limestone calcined clay cement system and a preparation method thereof. Background Art
[0002] Rail transit usually uses a DC traction power supply system, which means that power transportation is usually provided by conductor tracks that are not completely insulated from the ground. Therefore, when current flows through the rails, it is easy to leak, that is, stray current is generated, which poses a hidden danger to the concrete structure and the safety of passengers. In addition, subways are usually in underground environments and face the erosion of abundant groundwater and harmful ions, which puts higher requirements on the durability of cement-based materials. Therefore, a high-impedance cement-based material with excellent impedance and durability has been developed, which can not only effectively protect against the influence of stray currents and solve the hazards of step voltage on subway platform layers, but also improve the bearing capacity of building structures and enhance the durability of cement-based materials, thereby promoting the sustainable development of green building materials.
[0003] Factors that affect the conductivity of concrete include cement type, water-cement ratio, admixtures, curing methods, admixtures, etc. For example, the use of special mixing methods can improve the impedance value of concrete to a certain extent; and the addition of fly ash not only helps to refine the pore structure, but also can reduce the OH in the pore solution. - content, so that the resistivity of ordinary concrete is improved; the addition of husk ash as an admixture can also play a role in improving the resistivity of concrete. However, cement releases a large amount of carbon dioxide during the production process. Now a large number of scholars have adopted carbon reduction measures to improve this situation. The most commonly used method is to reduce the use of cement clinker by adding admixtures and low-clinker cement. For example, CN 117401913 A is a high-strength low-calcium cement suitable for carbonization curing and its preparation method, CN116282997A is a calcium carbonate cement, a calcium carbonate cement hardener and its application, and CN118125754A is a silica fume modified full coal gangue coarse aggregate concrete and its preparation method. However, the existing technical methods only consider the resistivity of the system or the mechanical properties of cement-based materials, and are not suitable for the application scenarios of rail transit. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a low-carbon high-impedance cement-based material based on a steel slag-hollow microsphere-limestone calcined clay cement system and a preparation method thereof. It is mainly aimed at optimizing the mix ratio of cement-based materials, by partially replacing cement or aggregates with limestone calcined clay cement (LC3), hollow glass microspheres, and carbonized steel slag, and adjusting the appropriate dosage of each component. Not only does it reduce carbon dioxide emissions, but it also improves the mechanical properties and durability of cement-based materials on the basis of improving the resistivity of the system, prolonging the service life of the structure, and is suitable for application scenarios in rail transit.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0006] On the one hand, a low-carbon high-impedance cement-based material based on a steel slag-hollow microsphere-limestone calcined clay cement system is provided, wherein the components include: limestone calcined clay cement 350-450kg / m 3 ; Hollow glass beads 65-75kg / m 3 ;Carbonized steel slag powder 80-100kg / m 3 .
[0007] Furthermore, its components also include: ordinary Portland cement 450-550kg / m 3 ; Silica fume 75-85kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0008] Furthermore, the silica fume is selected from 970U microsilica powder, the water reducer is selected from PC-200 polycarboxylic acid water reducer, and the aggregate is partially replaced by well-graded quartz sand.
[0009] On the other hand, a method for preparing the low-carbon high-impedance cement-based material based on the steel slag-hollow microsphere-limestone calcined clay cement system is provided, which comprises the following steps:
[0010] Step 1: Pass carbon dioxide into water to form a saturated carbonic acid solution;
[0011] Step 2: Mix the steel slag aggregate with the saturated carbonic acid solution and let it stand, and continue to introduce carbon dioxide to ensure that the solution is saturated with carbonic acid for 6 hours to obtain carbonized steel slag;
[0012] Step 3: drying, crushing and sieving the obtained carburized steel slag to remove excess unreacted materials and impurities to obtain carburized steel slag with suitable particle size;
[0013] Step 4: Finally, the screened carbonized steel slag is ground into powder and used to partially replace cement;
[0014] Step 5: Calculate and weigh the raw materials of each component according to the mix ratio of the experimental design;
[0015] Step 6: Add cement and admixtures into the mixer and stir for 2-4 minutes, then add quartz sand and stir for 2-4 minutes;
[0016] Step 7: Slowly add the steel fiber into the mixer to disperse it evenly, stir for 3-5 minutes, put it into the mold, and cover the molded specimen with plastic wrap;
[0017] Step 8: After the specimen is allowed to stand in air at 20±1℃ and relative humidity of 45±5%, it is demoulded and placed in saturated lime water for curing to the specified age.
[0018] The beneficial effects of the present invention are:
[0019] Calcined limestone cement (LC 3 ), hollow glass microspheres (HGM), and carbonized steel slag are added to partially replace cement or aggregate and adjust the appropriate dosage between the components. 3 Carbonized steel slag as a new type of green and environmentally friendly building material is conducive to reducing carbon dioxide emissions, promoting the sustainable development of building materials, and alleviating the huge pressure on the environment caused by development and construction. The accelerated carbonization of steel slag to form CaCO3 also has a favorable effect on the strength of the system. And HGM, as an insulating aggregate, its glass shell and the introduced closed pores block the effective propagation of current, thereby improving the resistivity of the cement system and reducing the harm of stray current. Therefore, the low-carbon high-impedance cement-based material based on the steel slag-hollow microsphere-limestone calcined clay cement system not only improves the resistivity of the system, but also improves the mechanical properties and durability of the cement-based material, thereby extending the service life of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 28d compressive strength of specimens with different mix ratios prepared in the examples;
[0021] Figure 2 28d resistivity of specimens with different mix ratios prepared in the examples. DETAILED DESCRIPTION
[0022] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0023] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0024] Embodiment 1:
[0025] A cement-based material, the specific ratio of which is: ordinary Portland cement 450-550kg / m 3 ; Calcined limestone clay cement (LC 3 )350-450kg / m 3 , silica fume 75-85kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0026] Embodiment 2:
[0027] A cement-based material, the specific ratio of which is: ordinary Portland cement 450-550kg / m 3 ; Calcined limestone clay cement (LC 3 )350-450kg / m 3 , silica fume 75-85kg / m 3 ;Carbonized steel slag powder 40-50kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0028] Embodiment 3:
[0029] A cement-based material, the specific ratio of which is: ordinary Portland cement 450-550kg / m 3 ; Calcined limestone clay cement (LC 3)350-450kg / m 3 , silica fume 75-85kg / m 3 ;Carbonized steel slag powder 80-100kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0030] Embodiment 4:
[0031] A cement-based material, the specific ratio of which is: ordinary Portland cement 450-550kg / m 3 ; Calcined limestone clay cement (LC 3 )350-450kg / m 3 , silica fume 75-85kg / m 3 ; Hollow glass beads 65-75kg / m 3 ;Carbonized steel slag powder 40-50kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0032] Embodiment 5:
[0033] A cement-based material, the specific ratio of which is: ordinary Portland cement 450-550kg / m 3 ; Calcined limestone clay cement (LC 3 )350-450kg / m 3 , silica fume 75-85kg / m 3 ; Hollow glass beads 65-75kg / m 3 ;Carbonized steel slag powder 80-100kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
[0034] The method for preparing the cement-based material of Example 1 comprises the following steps:
[0035] Step 1: Calculate and weigh the raw materials of each component according to the mix ratio of the experimental design;
[0036] Step 2: Add cement and admixtures into a mixer and stir for 2-4 minutes, then add quartz sand and stir for 2-4 minutes;
[0037] Step 3: Slowly add the steel fiber into the mixer to disperse it evenly, stir for 3-5 minutes, put it into the mold, and cover the molded specimen with plastic wrap;
[0038] Step 4: After the specimen is placed in air at 20±1℃ and relative humidity of 45±5% for 24 hours, it is demoulded and placed in saturated lime water for curing to the specified age.
[0039] The method for preparing the cement-based material of Example 2-5 comprises the following steps:
[0040] Step 1: Pass carbon dioxide into water to form a saturated carbonic acid solution;
[0041] Step 2: Mix the steel slag aggregate with the saturated carbonic acid solution and let it stand, and continue to introduce carbon dioxide to ensure that the solution is saturated with carbonic acid for 6 hours to obtain carbonized steel slag;
[0042] Step 3: drying, crushing and sieving the obtained carburized steel slag to remove excess unreacted materials and impurities to obtain carburized steel slag with suitable particle size;
[0043] Step 4: Finally, the screened carbonized steel slag is ground into powder and used to partially replace cement;
[0044] Step 5: Calculate and weigh the raw materials of each component according to the mix ratio of the experimental design;
[0045] Step 6: Add cement and admixtures into the mixer and stir for 2-4 minutes, then add quartz sand and stir for 2-4 minutes;
[0046] Step 7: Slowly add the steel fiber into the mixer to disperse it evenly, stir for 3-5 minutes, put it into the mold, and cover the molded specimen with plastic wrap;
[0047] Step 8: After the specimens are placed in air at 20±1℃ and relative humidity of 45±5% for 24 hours, they are demoulded and placed in saturated lime water for curing to the specified age.
[0048] Calcined limestone clay cement (LC 3) is an effective way to develop low-carbon cementitious materials. Its composition ratio is 30% calcined clay (CC), 15% limestone, 50% cement clinker and 5% gypsum. The application of this cement can significantly reduce the emission of greenhouse gases (carbon dioxide, CO2). During the hydration process, metakaolin (calcined clay) reacts with calcium hydroxide (Ca(OH)2, CH) generated by cement clinker to form pozzolanic reaction products, including aluminum-containing phases such as CASH gel. In addition, calcium carbonate (CaCO3) also reacts with calcium trialuminate (C3A) in the clinker to generate semi-carbon type hydrated calcium aluminate, etc. These reactions inhibit the conversion of calcium sulfoaluminite (AFt) to monosulfur type hydrated calcium sulfoaluminate (AFm). The result of these chemical reactions is to increase the replacement rate of clinker and form a more delicate and dense microstructure. At the same time, this structure can reduce the porosity of cement-based materials and increase the resistivity of the materials, thereby enhancing the strength and durability of the materials.
[0049] Hollow glass microspheres (HGM) consist of a glass shell and internal air and can be considered as insulating aggregates. The spherical shape and smooth surface of HGM act as a ball during the slurry mixing process, providing self-leveling ability. In addition, HGM can provide nucleation sites to promote water splashes in the early stage of hydration, and undergo a pozzolanic reaction in the later stage. Its activity is equivalent to that of kaolin or fly ash. This reaction improves the bonding between the matrix and HGM, so that the HGM shell after the reaction may become an effective barrier to maintain local stress and prevent the formation of microcracks in the ITZ. In addition, the glass shell of HGM and the air in its closed pores are non-conductive, blocking the propagation path of current. Therefore, the incorporation of HGM can effectively improve the resistivity of UHPC.
[0050] Calcium-containing minerals in steel slag, such as f-CaO, C3S, β-C2S, γ-C2S with low hydration activity, and calcium silicate (CaSiO3(CS)), can undergo carbonization reactions to form stable carbonized products and produce gelling properties, which can be used as building materials. After accelerated carbonization treatment, the strength of steel slag building materials is improved and the problem of poor stability is improved. In addition, steel slag accelerates carbonization to form CaCO3, which fills the pores and densifies the microstructure on the one hand, and on the other hand, the generated CaCO3 is embedded in the CSH product to form a composite reinforcement. Therefore, the addition of carbonized steel slag is beneficial to the improvement of system strength.
[0051] The present invention uses limestone calcined clay cement (LC 3 ), hollow glass microspheres (HGM) and carbonized steel slag are added to prepare high impedance ultra-high performance concrete. Under the same other experimental conditions, the electrical and mechanical properties of the specimens are tested respectively.
[0052] The compressive strength test was performed on the cement-based materials obtained in Examples 1-5, and the test results are shown in Table 1 (H0C0, H0C1, H0C2, H1C1, and H1C2 correspond to the cement-based materials obtained in Examples 1-5, respectively). 3 Not only can it achieve the sustainable development of building materials, its volcanic ash effect and physical filling effect can also improve the density of cement-based materials, thereby enhancing the mechanical properties. In addition, carbonized steel slag solves the problem of poor stability and is beneficial to the improvement of the strength of the cement system. Although the hollow structure of HGM destroys the continuity of the matrix and will reduce the mechanical properties to a certain extent, it provides nucleation sites in the early stage of hydration to promote hydration, and volcanic ash reaction occurs in the later stage to improve the bonding between the matrix and HGM. It can be seen from the test results that carbonized steel slag has a significant improvement on the mechanical properties of the cement matrix. Although HGM reduces the strength, it is still higher than the benchmark group.
[0053] Table 1 28d compressive strength of samples
[0054]
[0055]
[0056] The electrical properties of the cement-based materials obtained in Examples 1-5 were tested, and the resistivity test results are shown in Table 2. 3 The kaolin in cement will react with calcium hydroxide (Ca(OH)2, CH) generated by cement clinker to form pozzolanic reaction products, including aluminum-containing phases such as CASH gel, thereby improving the microstructure of the cement system. Admixtures such as silica fume not only undergo secondary hydration reactions with cement hydration products to improve the interface structure between cement and aggregate, but also because of their small particle size, they can fill the gaps between cement particles and reduce porosity, thereby further improving the resistivity of the material. It can be seen from the test results that both carbonized steel slag and hollow glass microspheres can improve the resistivity of the cement system to a certain extent, especially the single isolated pores associated with HGM are closed pores without water and are tightly wrapped by a dense matrix, which inhibits the conduction of current.
[0057] Table 2 Resistivity of sample 28d
[0058]
[0059] In summary, according to the concrete mix ratio provided by the present invention, a low-carbon cement-based material is obtained that can meet the requirements of mechanical properties and long-term durability, and can block the propagation path of current through the glass shell of hollow glass microspheres (HGM) and the air in its closed pores. Therefore, the addition of HGM can effectively improve the resistivity of UHPC. 3The addition of carbonized steel slag powder helps to reduce the amount of cement used, thereby alleviating the resource shortage and environmental pollution problems caused by over-exploitation in the construction and civil engineering fields, and promoting the development of building materials towards green, environmentally friendly and sustainable directions.
[0060] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A low-carbon, high-impedance cement-based material based on a steel slag-hollow microsphere-limestone calcined clay cement system, characterized in that: Its components include: limestone calcined clay cement 350-450kg / m 3 ; Hollow glass beads 65-75kg / m 3 ;Carbonized steel slag powder 80-100kg / m 3 .
2. The low-carbon high-impedance cement-based material based on the steel slag-hollow microsphere-limestone calcined clay cement system according to claim 1, characterized in that: Its components also include: ordinary Portland cement 450-550kg / m 3 ; Silica fume 75-85kg / m 3 ; Water reducing agent 6-7kg / m 3 ; Fine quartz sand 170-190kg / m 3 ; Coarse quartz sand 700-720kg / m 3 ; Steel fiber 70-80kg / m 3 ; Water 180-200kg / m 3 .
3. The low-carbon high-impedance cement-based material based on the steel slag-hollow microsphere-limestone calcined clay cement system according to claim 2, characterized in that: The silica fume is 970U microsilica powder, the water reducer is PC-200 polycarboxylic acid water reducer, and the aggregate is partially replaced by well-graded quartz sand.
4. The method for preparing a low-carbon high-impedance cement-based material based on a steel slag-hollow microsphere-limestone calcined clay cement system according to claim 2 or 3, characterized in that: The following steps are involved: Step 1: Pass carbon dioxide into water to form a saturated carbonic acid solution; Step 2: Mix the steel slag aggregate with the saturated carbonic acid solution and let it stand, and continuously introduce carbon dioxide to ensure that the solution is saturated with carbonic acid to obtain carbonized steel slag; Step 3: drying, crushing and sieving the obtained carburized steel slag to remove excess unreacted materials and impurities to obtain carburized steel slag with suitable particle size; Step 4: Finally, the screened carbonized steel slag is ground into powder and used to partially replace cement; Step 5: Calculate and weigh the raw materials of each component according to the mix ratio of the experimental design; Step 6: Add cement and admixtures into the mixer and stir for 2-4 minutes, then add quartz sand and stir for 2-4 minutes; Step 7: Slowly add the steel fiber into the mixer to disperse it evenly, stir for 3-5 minutes, put it into the mold, and cover the molded specimen with plastic wrap; Step 8: After the specimen is allowed to stand in air at 20±1℃ and relative humidity of 45±5%, it is demoulded and placed in saturated lime water for curing to the specified age.
Citation Information
Patent Citations
Calcium carbonate cement, calcium carbonate cement hardened body and application thereof
CN116282997A
High-strength low-calcium cement suitable for carbonization curing and preparation method thereof
CN117401913A
Silica fume modified full-coal gangue coarse aggregate concrete and preparation method thereof
CN118125754A